2015
DOI: 10.1111/pcn.12330
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of group cognitive behavioral therapy for somatoform pain disorder patients in Japan: A preliminary non‐case‐control study

Abstract: Aims: Somatoform pain disorder is associated with psychosocial dysfunction, and psychotherapies, such as cognitive behavioral therapy (CBT), are thought to provide useful interventions to address such dysfunction as well as the pain itself. However, little is known about whether CBT for somatoform pain disorder is effective, including the long-term course of the illness, in non-Western populations. We therefore tailored such a program based on an existing CBT protocol and examined its effectiveness in Japan.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…The theoretical model, rationale, and details of the CBT treatment have been previously described (Yoshino et al 2015). The major aims of treatment were to develop self-monitoring techniques that facilitate the identification of pain, thinking, behavior, and mood, to learn self-control techniques such as relaxation and behavioral activation, and to modify specific pain-related dysfunctional beliefs.…”
Section: Psychological Medicine 1149mentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical model, rationale, and details of the CBT treatment have been previously described (Yoshino et al 2015). The major aims of treatment were to develop self-monitoring techniques that facilitate the identification of pain, thinking, behavior, and mood, to learn self-control techniques such as relaxation and behavioral activation, and to modify specific pain-related dysfunctional beliefs.…”
Section: Psychological Medicine 1149mentioning
confidence: 99%
“…In terms of psychological interventions for chronic pain, cognitive-behavioral therapy (CBT) is reported to be useful, and is designed to modify maladaptive perceptual and behavioral patterns and to teach self-control techniques for pain management Yoshino et al 2015). However, to our knowledge, there are only a few neuroimaging studies that have investigated brain mechanisms modulated by CBT for patients with chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with persistent somatoform pain disorder (PSPD) are often characterized by a tendency to experience somatic symptoms in response to psychosocial stress . The efficacy of cognitive behavioral therapy (CBT) for PSPD has been demonstrated across clinical trials . Various studies, including our own, have shown that pain catastrophizing has an influence on the effect of pain intensity and pain‐related disabilities during CBT for somatoform disorders .…”
mentioning
confidence: 99%
“…The efficacy of cognitive behavioral therapy (CBT) for PSPD has been demonstrated across clinical trials . Various studies, including our own, have shown that pain catastrophizing has an influence on the effect of pain intensity and pain‐related disabilities during CBT for somatoform disorders . Pain catastrophizing is defined as the tendency to make an excessive broad interpretation of amplification and helplessness in the face of pain experience .…”
mentioning
confidence: 99%
See 1 more Smart Citation